ChemInform Abstract: Asymmetric Hydrogenation of 2‐Aryl‐5, 6‐dihydropyrazine Derivatives with Chiral Cationic Ruthenium Diamine Catalysts. Issue 13 (March 2015) - Li, Yong; He, Yanmei; Chen, Fei; Fan, Qinghua
Abstract The first asymmetric hydrogenation of 2‐substituted and 2, 3‐substituted 5, 6‐dihydropyrazines catalyzed by a chiral cationic Ru‐diamine complex affords chiral piperazine derivatives with good enantioselectivity and good yield.